Indigenous Community-Led Programs to Address Food and Water Security: Protocol for a Systematic Review - Ashleigh Chanel Hart (International Journal of Environmental Research and Public Health, 2021)
The connection between indigenous peoples and Country (a multidimensional concept including land and water) enabled communities to thrive and survive over millennia. This has been eroded by colonisation, dispossession and increasing food and water insecurity due to climate change and supply constraints. Globally, indigenous peoples experience a disproportionate burden of chronic disease and poor nutrition is a major risk factor. Indigenous leaders have been advocating for community-led solutions. The primary aim of this systematic review is to determine what community-led programs have been undertaken to address food and/or water security globally. A comprehensive search of peer-reviewed literature will be performed in EMBASE, CINAHL, PsycINFO, PubMed, Scopus, LILACs, Informit and Business Source Premier. The grey literature search will include grey literature databases, customised Google search engines, targeted websites, and consultation with experts. The search strategy will consist of four concepts, combined as follows: (1) indigenous peoples AND (2) community program AND (3) food security OR (4) water security. Covidence will be used for study screening and data extraction by two authors. A deductive thematic analysis using indigenous-informed methodologies will be used to synthesise data. This review seeks to provide insight on models and mechanisms to encourage action and metrics for quantifying success of indigenous community-led programs to improve food and water security.